Mechanical properties of concrete using ferronickel slag as fine aggregate and supplementary cementitious material - Saha, Ashish; Sarker, Prabir (Concrete Institute of Australia, 2018)
This study evaluates the combined use of granulated ferronickel slag (FNS) as fine aggregate and ground granulated ferronickel slag (GFNS) as a supplementary cementitious material (SCM) in concrete. Test results show that 30% cement replacement by GFNS reduced the 28-day compressive strength. However, gradual strength development continued to 180 days by the pozzolanic reaction of GFNS. Strength of concrete also improved with the increment of FNS fine aggregate up to 50% due to the improved grading of aggregate. The correlations of tensile strength, flexural strength and elastic modulus with compressive strength were not affected by the use of GFNS and FNS aggregate. Overall, the mechanical properties of concrete using 30% GFNS as SCM together with 50% FNS as fine aggregate were similar to those of control concrete after 56 days of age. Thus, use of GFNS and FNS aggregate can be considered as a viable option for producing green concrete.